2021
DOI: 10.1111/tmi.13647
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic costs among tuberculosis‐affected households in Zimbabwe: A national health facility‐based survey

Abstract: Objectives To determine the incidence and major drivers of catastrophic costs among TB‐affected households in Zimbabwe. Methods We conducted a nationally representative health facility‐based survey with random cluster sampling among consecutively enrolled drug‐susceptible (DS‐TB) and drug‐resistant TB (DR‐TB) patients. Costs incurred and income lost due to TB illness were captured using an interviewer‐administered standardised questionnaire. We used multivariable logistic regression to determine the risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…FRP studies on CDs (n = 13) were mostly concerned with tuberculosis (TB) in LwMICs (n = 7) (Additional file 5). CHE due to TB could be as high as 80% (Zimbabwe) despite the availability of free treatments in public facilities [45]. Drug-resistant TB was responsible for about 14% to 65% higher burden than the drug-susceptible variety [45,46].…”
Section: Cds and Maternal And Perinatal Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…FRP studies on CDs (n = 13) were mostly concerned with tuberculosis (TB) in LwMICs (n = 7) (Additional file 5). CHE due to TB could be as high as 80% (Zimbabwe) despite the availability of free treatments in public facilities [45]. Drug-resistant TB was responsible for about 14% to 65% higher burden than the drug-susceptible variety [45,46].…”
Section: Cds and Maternal And Perinatal Conditionsmentioning
confidence: 99%
“…CHE due to TB could be as high as 80% (Zimbabwe) despite the availability of free treatments in public facilities [45]. Drug-resistant TB was responsible for about 14% to 65% higher burden than the drug-susceptible variety [45,46]. Note that, in line with WHO's End TB Strategy to end the global TB epidemic, most TB studies defined OOP expenses as the sum of direct medical, Fig.…”
Section: Cds and Maternal And Perinatal Conditionsmentioning
confidence: 99%
“…However, the recent cost survey conducted in Zimbabwe, showed that 90% of DR-TB affected households experience catastrophic costs, highlighting the vulnerability and low socioeconomic status of most of these households. (11)…”
Section: Discussionmentioning
confidence: 99%
“…Major drivers of catastrophic costs are outside the health system and include food, transport, and income loss. Across settings, DR-TB affected households incur higher costs than households affected by drug-susceptible TB, (9)(10)(11)(12)(13)(14) which may push households into financial catastrophes, and may act as barriers to accessing TB diagnostic and treatment services. (15) The End TB strategy acknowledges the need for greater action on the social determinants of TB through implementing universal health coverage and social protection.…”
Section: Introductionmentioning
confidence: 99%
“…The direct and indirect costs supported by these millions of people in need of care are both the cause and the consequence of the socio-economic impact of TB on the poorest populations 2 4 . In this sense, inadequate access to care is a major contributor to the dramatic spiral of poverty and uncontrolled disease transmission.…”
Section: Introductionmentioning
confidence: 99%